The object-oriented dynamic task assignment for unmanned surface vessels. (November 2021) - Du, Bin; Lu, Yu; Cheng, Xiaotong; Zhang, Weidong; Zou, Xuesong
Abstract: This paper investigates the task assignment and guidance issues of unmanned surface vessels (USVs) interception. When the USVs formation is invaded by some moving objects during its escort, it is necessary for the unmanned systems to assign defenders to prevent attackers approaching the vulnerable target in antagonistic scenarios. This action requires efficient guidance and task assignment strategies. With this in mind, this paper presents the Integral Proportional Navigation Guidance (IPNG) with Tabu Dynamic Consensus-Based Auction Algorithm (TDCBAA) in marine interception scenario. First, IPNG is introduced in the interception game considering the USV kinematic model, which can effectively reduce the individual interception time. Second, a new bidding function is designed for moving objects interception with the consideration of the attackers' types, positions and interception time. Finally, a TDCBAA is designed to solve the task assignment subproblem, resulting in a shorter overall interception time and a higher interception success rate. Simulations demonstrate that the proposed algorithm can optimize the allocation of defenders in real-time and intercept the attackers more quickly compared with other classical algorithms, which is more suitable in situations where attackers are approaching from all directions. Highlights: The Integral Proportional Navigation Guidance law is developed to guide defenders track attackers. The Tabu Dynamic Consensus-Based Auction Algorithm is proposed for USVs task assignment using Tabu optimization and dynamic relocation. A novel bidding function is designed for moving objects interception with the consideration of the attackers' types, positions and interception times. We firstly design a system combining guidance and task assignment for interception game based on dynamic model.